RI 3311 Cooperative Fuel Research Motor-Gasoline Survey, Winter 1935-36 ? Introduction (f79401a8-bdde-406e-858a-1baa09149753) (The National Institute for Occupational Safety and Health (NIOSH), 1936)
This is the first publication in a projected series of reports on properties of commercial motor fuels pursuant to a cooperative agreement between the Cooperative Fuel Research (C.F.R.) Committee and the Bureau of Mines of the Department of the Interior. The report gives results of analyses in oil-company laboratories of sample of gasoline obtained from service-station pumps in 18 marketing areas by representatives of oil companies. These companies obtained the samples and analyzed them for their own information and supplied data from their laboratory reports to the Bureau of Mines for compilation and publication. History of Bureau of Mines Gasoline Surveys The following quotation from Report of Investigations 31624/ is included in this place for the information of readers who are not familiar with the Bureau of Mines gasoline surveys that have preceded the present report: